Wrongs and faults - Gardner, J (Oxford University Press, 2005)
This chapter begins with a discussion of 'the elementary moral distinction'. It then considers lives and wrongs, people and faults, fault-anticipating wrongs, and the fault principle. It argues that moral philosophy has lost sight of the need to rely on the deservedness of punishment to explain punishment's meanings and consequences. In the process it has lost sight of the need to explain, in a way that does not depend on punishment's meanings or consequences, why the only actions that deserve to be punished are both wrongful and blameworthy (two different and only very obliquely related properties).